Corneal endothelium assessment through specular microscopy in participants with diabetic macular edema - Sabino, Bárbara (2024)
Introduction: While the morphological and functional integrity of the corneal endothelium, which is essential for corneal transparency, is affected by diabetes mellitus (DM), its relationship with the severity of diabetic retinopathy and the presence of diabetic macular edema is unclear. Aims: To assess the morphological characteristics of the corneal endothelium in patients with Type 2 Diabetes Mellitus (T2DM) with different therapeutic response profiles to diabetic macular edema (DME). Methods: With a cross-sectional approach, 24 participants with T2DM were divided into 2 groups (without DME versus with DME). Subsequently, the group with DME was subdivided according to the type of therapeutic response (responder versus persistent). Parameters obtained through specular microscopy (endothelial cell density, coefficient of variation, hexagonality, and central corneal thickness) and optical coherence tomography (minimum foveal thickness, central 1mm thickness, macular ganglion cell layer thickness, and peripapillary retinal nerve fiber layer thickness) were analyzed and compared in the different groups. Results: No significant changes were found in the corneal endothelium between the groups with and without DME (p>0.05). However, differences were found in the density of endothelial cells (p=0.04) in participants with persistent DME (1900.3 ± 270.1) compared to participants with responding DME (2307.9 ± 121.2) and control group (2191.7 ± 165.5). Conclusion: There were no differences in the different parameters of the corneal endothelium between participants with and without DME. However, the kind of therapeutic response to DME seems to be associated with a decrease in endothelial cell density.